(untitled) (Web of Teachers: Inderscience Research, 2025)
The article focuses on the contributions of Russian scholars and travelers to the study of the history of the peoples of the Southern Aral Sea region, both in political and socio-economic terms. Members of the 1873 and 1874 scientific expeditions left a rich historical and ethnographic material about the population of the lower reaches of the Amu Darya, which opens new pages in the history of the native land.